"It Was All Wrong and Shameful to Beat Her": Discursive Analysis of Men's Talk of Intimate Partner Violence. (March 2023) - Dery, Isaac; Akurugu, Constance Awinpoka; Baataar, Cuthbert
In this article, our aim is to foreground men's discourses on gender-based violence as linked to gendered hierarchies, power struggles, and social respectability in Ghana. Situated within decolonial feminist theories and drawing on interviews, we argue that men's interpretations of masculinity and the possibility of perpetrating violence against women is significantly mediated by such intersectional factors as sociocultural background, education, and broader societal normative requirements. The findings deepen the understanding of the ambiguities and contradictions that characterize men's talk of violence. The article discusses how these ambiguities and contradictions serve as important domains for engendering critical attitudes toward violence against women.